Serological detection for Entamoeba histolytica among cancer patients suffering from diarrhea in Thi-Qar province/ Southern Iraq - Hameed, Fadhil; Khalaf, Amal (University of Thi-Qar Journal of Science, 2022)
AbstractCancer is a state in which cell proliferation occurs abnormally when it becomes uncontrollable and able to invade other cells. Additionally, the number of cancer patients has been clearly rising in recent years. Therefore, it is necessary to study the incidence of intestinal parasites infections in people with this diseas and understand how harmful that is. Cancer patients with parasitic infections were a targets in the current study. The present study was carried out during the period of July through December 2022 in Thi-Qar province. The total number of samples was 70 cancer patients, blood samples were collected from them and examined via the ELISA system to detect the infection with intestinal parasites (Entamoeba histolytica ). Total number of a positive patients for intestinal parasite E.histolytica were 11(15.7%) , analysis of serum samples for anti-amebic antibodies revealed that (15.7% and 2.85% of samples) were positive for IgG and IgM respectively, while negative for IgA. According to the ELISA findings, E. histolytica was the most common intestinal parasite that caused diarrhea that was reported among patients with cancer.